Neuroactive steroids protect retinal pigment epithelium against oxidative stress - Bucolo, Claudio (2005)
This study was undertaken to assess whether neuroactive steroids, 17β-estradiol and dehydroepiandrosterone-sulfate, enhance survival and protect DNA of human retinal pigment epithelial cells challenged by oxidative stress, and to investigate the role of σ(1) receptors in the effects of neuroactive steroids. Retinal pigment epithelial cells were treated with various concentrations of neuroactive steroids and then exposed to hydrogen peroxide. Pretreatment with steroids resulted in significant increased viability in a dose-related manner. DNA damage induced by oxidative insult was significantly lower with steroid pretreatment. The effects of 17β-estradiol and dehydroepiandrosterone-sulfate were antagonized by pretreatment with a σ(1) receptor antagonist. The results suggest that neuroactive steroids protect retinal cells from oxidative stress, and that this effect is mediated by σ(1) receptors.